A new observable in extensive air showers - García Canal, Carlos Alberto (2016)
We find that the ratio rμe of the muon to the electromagnetic component of an extended air shower at the ground level provides an indirect measure of the depth Xmax of the shower maximum. This result, obtained with the air-shower code AIRES, is independent of the hadronic model used in the simulation. We show that the value of rμe in a particular shower discriminates its proton or iron nature with a 98% efficiency. We also show that the eventual production of forward heavy quarks inside the shower may introduce anomalous values of rμe in isolated events.